Empowering Kampung Kerupuk Community through Improving the Technology of the Crackers Drying Process in Tambakrejo Village, Sidoarjo Regency - Falasifah, Nihlatul; Ningsih, Yusria; Aqidah, Jazilia Hikmi Nur; Haq, Achmad Zihaul; Hakim, Adiyaksa Lukmanul (Jurnal Soeropati, 2024)
This activity focuses on improving the technology of the crackers drying process to enhance the quality and efficiency of crackers products for the â€œKampung Kerupukâ€ community in Tambakrejo Village, Sidoarjo Regency. The main issue addressed is the conventional method of crackers drying, reliant solely on sunlight, leading to difficulties, especially during the rainy season. The methodology employed in this community service is Participatory Action Research (PAR), actively involving the â€œKampung Kerupukâ€ community in every activity. The achieved outcomes of the community service activities are evident through the improvement observed in pretest to post-test scores during the socialization and education on the technology of crackers drying. The pretest and post-test results exhibit an increase, with an average pretest score of 40 rising to 84 in the post-test. The community service has generated several outputs, including an understanding of crackers drying technology, the creating of an appropriate technology in the form of a crackers drying machine powered by LPG, and the establishment of the organizational structure for the â€œKampung Kerupukâ€ community. This appropriate technology proves instrumental in improving the quality and efficiency of crackers production for the â€œKampung Kerupukâ€ in Tambakrejo Village, Sidoarjo.